Minimal intervention dentistry: minimizing the restoration cycle: Literature review - Naccha Torres, Andres (2021)
Objective: to present the current concepts of Minimal Intervention Dentistry with an emphasis on minimizing the restoration cycle. Materials and methods: a bibliographic search of articles in English and Spanish was carried out in databases: Pubmed, with the words: dental caries, minimal invasive dentistry; Also, Google Scholar search was used with the keywords: dental caries, minimal intervention dentistry, tooth structure and dental remineralization in articles published between 2016 and 2020.  Results: the sample consisted of 40 scientific publications, including a literature review, systematic reviews and meta-analysis, case reports, complete original articles referring to deciduous and mixed dentition, and minimal intervention treatment alternatives. Conclusions: the objective of Minimal Intervention Dentistry is to avoid unnecessarily removing healthy dental tissue, avoiding the use of the high-speed handpiece and reducing the restoration cycle, allowing to reduce work time, stress for pediatric patient and placement of anesthesia. Treatment alternatives within the MID premise are shown to dentists so they can use them in their pediatric patients according to the clinical cases that are presented to them.